The rights of nature and the need to move towards a new ontology - Monteagudo, Cecilia (2023)
The utilitarian approach, normalized by humans as a way to relate with other non-human forms of life has led us to build a lifestyle that has generated irreparable and irreversible environmental damages. In such context, this article offers a complex view from some voices of contemporary hermeneutics about the relationship between nature and its possibility of accessing rights. For this purpose, research is divided into four sections. We initially propose a review of the links between anthropocentrism, modern law and the construction of the modern subject’s identity. Next, an interpretation of the search and production of knowledge as an activity capable of causing destructive effects to the environment is offered in relation to the previous ideas. Then, such perspective is complemented by a reflection on the myth of scientific objectivism, as a homogenizing attitude that colonizes different cultural spheres. Finally, we address the domination of nature by human beings as a practice that reflects the utilitarian bond through which we have organized our way of life. This invites us to think about the need to move towards a new ontological paradigm that allows us to build a non-hierarchical and non-exclusive approach to non-human forms of life.